2019
DOI: 10.3389/fphys.2019.00998
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear Amplification of Variability Through Interaction Across Scales Supports Greater Accuracy in Manual Aiming: Evidence From a Multifractal Analysis With Comparisons to Linear Surrogates in the Fitts Task

Abstract: Movement coordination depends on directing our limbs to the right place and in the right time. Movement science can study this central requirement in the Fitts task that asks participants to touch each of two targets in alternation, as accurately and as fast as they can. The Fitts task is an experimental attempt to focus on how the movement system balances its attention to speed and to accuracy. This balance in the Fitts task exhibits a hierarchical organization according to which finer details (e.g., kinemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 92 publications
1
44
0
Order By: Relevance
“…We conduct a replication study (N=28), and two new experiments (N=44, N=30), using MFA to analyse recordings of hand movement on a mouse during a game, in order to estimate the multifractality of the hand movement. Multifractality is a measure of complexity which has previously been linked to skill [7], adaptive behaviour [4], and readiness-to-hand during tool breakdown [23]. The results of our three experiments show that multifractality in hand movement correlates with level of engagement, and two other features of readiness-to-hand: the adequacy of the tool, and familiarity with the tool.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…We conduct a replication study (N=28), and two new experiments (N=44, N=30), using MFA to analyse recordings of hand movement on a mouse during a game, in order to estimate the multifractality of the hand movement. Multifractality is a measure of complexity which has previously been linked to skill [7], adaptive behaviour [4], and readiness-to-hand during tool breakdown [23]. The results of our three experiments show that multifractality in hand movement correlates with level of engagement, and two other features of readiness-to-hand: the adequacy of the tool, and familiarity with the tool.…”
Section: Introductionmentioning
confidence: 60%
“…with flexibility and adaptation, executive function, skill, and engagement [4,7,58]. This role in flexible behaviour has been explained both in terms of genesis and function.…”
Section: Multifractality In Adaptive Human Behaviour Multifractalitymentioning
confidence: 99%
See 1 more Smart Citation
“…That is, a single degree of freedom can exhibit different fractal patterns across time or for different-sized events. For that matter, perceptual accuracy may depend sooner on the nonlinearity generating multifractal forms than on nonlinearity generating monofractal forms [24,[32][33][34]. The difference here has to do with the fact that monofractal form is only suggestive of a similar pattern observable at many scales, and it is mute to the reasons for similarity.…”
Section: Could Flow Of Multifractal Fluctuations Support Perception Vmentioning
confidence: 95%
“…Visually fixating brings a prestressed quiet stance into one with informational coupling with the visual stimulus. Past work has repeatedly implicated fractal fluctuations in the head and upper torso for using visual information to organize action [28,29,[65][66][67][68]. Visual inspection of IRF plots indicated rare instances of effects from or responses from CoM fractality on or to SD (1 trial in the 50-, 135-, and 305-cm conditions), but the regression modeling indicated no stable relationship.…”
Section: Glimpses Of a Possible Control Policy For Visually Guided Qumentioning
confidence: 99%